Experience with cellulose acetate-coated activated charcoal haemoperfusion in the treatment of severe hypnotic drug intoxication. Issue 661 (November 1980) - Crome, P.; Hampel, G.; Widdop, B.; Goulding, R.
Abstract : A haemoperfusion column containing activated charcoal coated with cellulose acetate was used to treat 7 patients with barbiturate or ethchlorvynol poisoning. Six of the patients showed marked lightening of coma and all showed a significant fall in plasma drug concentration. Plasma drug clearance and platelet loss were similar to those reported for other coated charcoal columns. Cellulose acetate-coated charcoal haemoperfusion may reduce the period of coma in severe poisoning with barbiturates and other hypnotic drugs and thus the morbidity and mortality.